Current issues in non-timber forest products research. Proceedings of the workshop research on NTFP. Hot Spring, Zimbabwe, 28 August - 2 September 1995 - Ruíz Pérez, M.; Arnold, J.E.M. (Center for International Forestry Research, 1996)
This book contains a number of commissioned background papers presented at the workshop on ‘Research on Non-timber Forest Products’ (Hot Springs, Zimbabwe, 28 August - 2 September 1995). Bringing together experiences from different regions and professional backgrounds, the book attempts to analyse the complexity of multiple use of forests from a multidimensional perspective that incorporates environmental, social, economic, technological, political, historical and cultural factors. Current topics of discussion are reviewed. These include the possibility of matching the conservation and development agendas through promoting NTFPs as proposed by a number of initiatives, the unidirectional path of development from extraction to intensive agricultural production, the roles of NTFPs in people’s livelihood strategies, the internal differentiation amongst communities, the different forms of actions adopted to secure tenure and their diverging effects, as well as the meaning and convenience of using NTFPs as an analytical category. A general conclusion to be drawn from the book is the need to build up an interdisciplinary research agenda, as well as to employ more than one approach or method in addressing the complex situations that characterise the multiple use of forests.